1985
DOI: 10.1128/jvi.56.3.930-937.1985
|View full text |Cite
|
Sign up to set email alerts
|

Passive immune protection by herpes simplex virus-specific monoclonal antibodies and monoclonal antibody-resistant mutants altered in pathogenicity

Abstract: Virus-neutralizing monoclonal antibodies specific for 13 different genetically defined epitopes of glycoproteins gC, gB, and gD of herpes simplex virus type 1, strain KOS-321, were compared for their ability to provide passive immunity to DBA-2 mice challenged intracranially. Protection was highly specific, since individual monoclonal antibodies failed to protect against infection with monoclonal antibody-resistant (mar) mutants altered in the single epitope recognized by the injected antibody. The dose-respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(16 citation statements)
references
References 22 publications
0
14
1
1
Order By: Relevance
“…However, this glycoprotein may play an important role in natural infection because nearly all clinical isolates of HSV-1 express gC (25,32). Indeed, a gCmutant of HSV-1 (strain KOS) is less pathogenic than wild-type virus following intracranial inoculation of mice (17).…”
mentioning
confidence: 99%
“…However, this glycoprotein may play an important role in natural infection because nearly all clinical isolates of HSV-1 express gC (25,32). Indeed, a gCmutant of HSV-1 (strain KOS) is less pathogenic than wild-type virus following intracranial inoculation of mice (17).…”
mentioning
confidence: 99%
“…A consistent positive correlation was found between ELISA antibody titres to gD-1, and titre in all the other assays. Monoclonal antibodies to gD are capable of neutralizing virus in the absence of complement, and of mediating CMC and ADCC [3,4]. Western blots probed with sera from our vaccinated guinea pigs have shown that there is a more pronounced response to gD than to the other virion glycoproteins (data not shown).…”
Section: Discussionmentioning
confidence: 84%
“…Attempts have been made to correlate the ability to protect with activity and in vitro functional assays, i.e., antibody and complement-mediated cytotoxicity (CMC), antibody-dependent cellular cytotoxicity (ADCC), and neutralization with or without complement. However, such associations have not been conclusively demonstrated [3][4][5]. In the present study we vaccinated guinea pigs with a HSV 1 subunit vaccine [6], and subsequently challenged them intravaginally with HSV 2.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The SVV gC is nonessential for viral replication in cell culture, but may be important in viral pathogenesis (Gray and Byrne, 2003). HSV-1, bovine herpesvirus type 1 (BHV-1), and equine herpesvirus type 1 (EHV-1) gC mutants are attenuated (Kumel et al, 1985;Kúdelová et al, 1991;Kaashoek et al, 1998;Osterrieder, 1999). The VZV gC is associated with virion morphogenesis in the skin and VZV gC mutants have restricted ability to replicate in skin tissue in SCIDhu mice (Moffat et al, 1998,Storlie et al, 2006) and a defective gC has been proposed as the basis of attenuation for the VZV Oka vaccine (Kinchington et al, 1990).…”
Section: Discussionmentioning
confidence: 99%